If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-3y + 1) = 8y + 1 Reorder the terms: -1(1 + -3y) = 8y + 1 (1 * -1 + -3y * -1) = 8y + 1 (-1 + 3y) = 8y + 1 Reorder the terms: -1 + 3y = 1 + 8y Solving -1 + 3y = 1 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. -1 + 3y + -8y = 1 + 8y + -8y Combine like terms: 3y + -8y = -5y -1 + -5y = 1 + 8y + -8y Combine like terms: 8y + -8y = 0 -1 + -5y = 1 + 0 -1 + -5y = 1 Add '1' to each side of the equation. -1 + 1 + -5y = 1 + 1 Combine like terms: -1 + 1 = 0 0 + -5y = 1 + 1 -5y = 1 + 1 Combine like terms: 1 + 1 = 2 -5y = 2 Divide each side by '-5'. y = -0.4 Simplifying y = -0.4
| -4y+9y=-6+9 | | 4v+6v=10 | | 30+5j=45 | | 2(7v-3)=20v-6(v+1) | | 9x-13=31 | | 4x+9=6x+7 | | 25k^4-1=0 | | -4(-12-15b)=-5(-12b-12) | | 5x-20=3(x-4) | | -7p=42 | | -5/2(w-1)+3=18 | | X-4-3x=-2x-4 | | b-4=3b | | 12=-3v+6b | | -7(-2g+4)+19=-9+14g | | 3(n-4)=-42 | | 9(2X+5)=3X | | 1x+2=4x-12 | | 11-4c=3 | | 3(x-14)+(x+30)/5=x+2(3x-15)/5 | | (x+7)(2x-3)=140 | | 7x+1=8-4x | | -45+8v=-3(1+10v)-4v | | -10+14u=-8(-3u+15) | | x+2x+x-12=180 | | 25=4.5+12 | | -(-10t+2)+6=8-3t | | -3(-10-4s)=-2(-15-6s) | | 0=n-1-3 | | 21=15+4(m-2) | | Y(3x-4)=3(x-2) | | 10+x=4x+2x |